PENINGKATAN OMSET UKM BINTANG MELALUI MESIN TEKNOLOGI TEPAT GUNA PANGGANG AYAM - Sugiharto, Mulus; Suprobowati, Dewi; Subaderi, Subaderi (LPPM Universitas Sangga Buana, 2025)
One example of a business in the food service sector is a katering service that provides food orders to be delivered to various places according to customer needs. Elysabeth Annete, Chairperson of Bintang Surabaya's SME Partners, acted as a sponsor for the SMEs this year. However, the partners faced several obstacles, such as limited production capacity that was unable to meet market demand. This is due to the use of traditional (slow) meat processing machines, production processes that rely on manual equipment, and the lack of ability to manage finances independently. The objectives of this Student Creativity Program (PKM) are to increase the production capacity and quality of partner machines by applying appropriate technology. Increase partner income through increased production capacity. The program implementation method includes planning, implementation, monitoring and evaluation, success indicators, and program achievement targets. The focus of this experiment is to increase design pressure through the application of Appropriate Technology (TTG) on Chicken Roasting Machines, so as to increase production capacity and product quality. As a result, the partners successfully completed the training and adjustment program in accordance with the guidelines from the PKM UWP team.